2017
DOI: 10.15407/ubj89.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Changes in proHB-EGF expression after functional activation of the immune system cells

Abstract: The intensity of oxidative stress, protein expression of antiapoptotic Bcl-2 as well as antioxidant enzymes manganese superoxide dismutase (MnSOD) and glutathione peroxidase (GPx) and their regulator p53 were studied in the mitochondria of rat heart. Sessions of repeated hypoxia/reoxygenation ((h/r) A large body of experimental data indicates that reactive oxygen species (ROS) play a fundamental role in hypoxia/reoxygenation injury of cells and subcellular structures [1]. Mitochondria are considered an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, the enzyme activity of CAT and GPx increased (Figure 2C). CAT and GPx mRNA expression was probably time-dependent [43]. It has been reported that mRNA half-lives were about several minutes to several hours.…”
Section: Discussionmentioning
confidence: 99%
“…However, the enzyme activity of CAT and GPx increased (Figure 2C). CAT and GPx mRNA expression was probably time-dependent [43]. It has been reported that mRNA half-lives were about several minutes to several hours.…”
Section: Discussionmentioning
confidence: 99%